Identification of PGRMC1 as a Candidate Oncogene for Head and Neck Cancers and Its Involvement in Metabolic Activities - Zhao, Yue; Ruan, Xiangyan (Frontiers in Bioengineering and Biotechnology, 2020)
Progesterone Receptor Membrane Component 1 (PGRMC1/Sigma-2 receptor) is located on chromosome Xq21 and encodes a haem-containing protein that interacts with epidermal growth factor receptor (EGFR) and cytochromes P450, with function in tumor proliferation and chemoresistance. Although the over-expression of PGRMC1 reported in many different types of human cancers, systematic analysis of its oncogenic role of PGRMC1 has not been performed for any cancer. In this work, we analyzed the transcriptomics, genomics, and clinical data of 498 head-neck squamous cell carcinoma (HNSC) samples from the public-accessible database, The Cancer Genome Atlas (TCGA). The Cox regression was performed to calculate the hazard ratio (HR) of PGRMC1 expression as a prognosis feature for overall survival (OS). Our results demonstrated that PGRMC1 expression served as a predictor for worse OS (HR=1.95, P=0.0005) in head-neck squamous cell carcinoma. And the over-expression of PGRMC1 was strongly correlated with various metabolic process activity as well as cancer metastasis and cell proliferation features in human head-neck squamous cell carcinoma patient’s cohort. Besides, the over-expression and unfavorable prognosis value of PGRMC1 were also observed in many other cancer types. This study provides insights into the potential oncogenic functional significance of PGRMC1 in cancer research.